Weak self-sustained system under the actions of less weak excitations - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 1994)
It has been known that, in several cases, to study quasi-linear oscillating system, the degrees of smallness of various factors must be distinguished in detail [2-7]. To affirm again this interesting remark, we shall examine a weak (of order ε2) self-sustained system subjected to less weak (of order ε) excitations in resonance cases. It will be seen that the system considered is enhanced.